Effects of hall current on unsteady hydromagnetic free convection flow past an impulsively moving vertical plate with Newtonian heating - Seth, Gauri Shanker; Sarkar, Subharthi; Sharma, Ria (Zielona Góra: Uniwersytet Zielonogórski)
An investigation of unsteady hydromagnetic free convection flow of a viscous, incompressible and electrically conducting fluid past an impulsively moving vertical plate with Newtonian surface heating embedded in a porous medium taking into account the effects of Hall current is carried out. The governing partial differential equations are first subjected to the Laplace transformation and then inverted numerically using INVLAP routine of Matlab.
Keywords: hydromagnetic free convection flow; Newtonian heating; Hall currents; porous medium; INVLAP routine in Matlab